The Influence of Taxpayer Awareness, Digital Tax Literacy, and Service Quality on Taxpayer Compliance in Pamekasan Regency - Rini Nur Hayati; Nurul Alfian; Subhan; Rohmaniyah (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of taxpayer awareness, digital tax literacy, and service quality on individual taxpayer compliance in Pamekasan Regency. The research employed a quantitative approach with an associative method. The sample consisted of 97 individual taxpayers selected using an accidental sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS version 26. The results show that taxpayer awareness, digital tax literacy, and service quality have a positive and significant effect on taxpayer compliance. Simultaneously, the three independent variables explain 59.1% of the variation in taxpayer compliance, while the remaining 40.9% is influenced by other factors outside the research model. These findings emphasize the importance of improving taxpayer awareness, strengthening digital tax literacy, and enhancing service quality to encourage sustainable taxpayer compliance.